Procyclicality in the Financial System: Do We Need a New Macrofinancial Stabilization Framework? - William R. White (Kiel Institute for World Economics (IfW), 2005)
Economic liberalization almost everywhere has constituted a positive supply shock which has been profoundly disinflationary at the global level. Financial liberalization in the industrial countries has also given fuller rein to inherent tendencies towards “procyclicality”, a process of credit creation leading to asset price increases and heavy fixed investment which can amplify the business cycle. Monetary authorities in the industrial countries have generally been able to follow easier policies than otherwise given the absence of inflationary pressures. Monetary authorities in emerging market economies, particularly in Asia, have also eased in an attempt to offset the upward pressure on their currencies resulting from ease elsewhere. Given this combination of circumstances, there has been no systematic resistance to the financial sector's inherent tendencies to overreach. Adept countercyclical monetary policies have to date mitigated the potential economic costs of these imbalances. However, these policies have also had less welcome cumulative effects over time. The first is that nominal policy rates were ratcheted down very close to the zero nominal bound. This raises issues having to do with the potential for future policy responses in the event of further shocks threatening growth and employment. The second by-product has been that the financial imbalances have tended to grow ever larger. Consider the low level of saving in the United States, the current high level of fixed investment in China, rising house prices almost globally, and growing external imbalances as well. The paper concludes that the global economy does face exposures warranting a policy response. The challenge for domestic authorities looking forward is how the likelihood of a recurring imbalances might be reduced while still maintaining the benefits of financial liberalization. Two principles might underly such a domestic macrofinancial stabilization framework. First, we need closer cooperation between the domestic official agencies concerned about financial stability. Second, a more symmetric response from both monetary and regulatory authorities to the expansionary and contractionary phases of endogenous financial cycles might be suggested. In this regard, more attention needs to be paid to the source of disinflationary and even deflationary forces, since history indicates that they are not all equally dangerous. The parallel issue of whether we need a macrofinancial stabilization framework at the international level is also discussed. Unlike earlier international financial systems, there is no mechanism in the current “hybrid” system to prevent external imbalances from becoming so large as to threaten an eventual disorderly adjustment.
Keywords: 330; Finanzsektor; Konjunktur; Finanzmarktkrise; Geldpolitik; Bankenaufsicht; Internationale wirtschaftspolitische Koordination; Internationale Währungspolitik; Welt